microRNAs Sculpt Neuronal Communication in a Tight Balance That Is Lost in Neurological Disease - Thomas, Kristen T.; Gross, Christina; Bassell, Gary J. (Frontiers in Molecular Neuroscience, 2018)
Since the discovery of the first microRNA 25 years ago, microRNAs (miRNAs) have emerged as critical regulators of gene expression within the mammalian brain. miRNAs are small noncoding RNAs that direct the RNA induced silencing complex to complementary sites on mRNA targets, leading to translational repression and/or mRNA degradation. Within the brain, intra- and extracellular signaling events tune the levels and activities of miRNAs to suit the needs of individual neurons under changing cellular contexts. Conversely, miRNAs shape neuronal communication by regulating the synthesis of proteins that mediate synaptic transmission and other forms of neuronal signaling. Several miRNAs have been shown to be critical for brain function regulating, for example, enduring forms of synaptic plasticity and dendritic morphology. Deficits in miRNA biogenesis have been linked to neurological deficits in humans, and widespread changes in miRNA levels occur in epilepsy, traumatic brain injury, and in response to less dramatic brain insults in rodent models. Manipulation of certain miRNAs can also alter the representation and progression of some of these disorders in rodent models. Recently, microdeletions encompassing MIR137HG, the host gene which encodes the miRNA miR-137, have been linked to autism and intellectual disability, and genome wide association studies have linked this locus to schizophrenia. Recent studies have demonstrated that miR-137 regulates several forms of synaptic plasticity as well as signaling cascades thought to be aberrant in schizophrenia. Together, these studies suggest a mechanism by which miRNA dysregulation might contribute to psychiatric disease and highlight the power of miRNAs to influence the human brain by sculpting communication between neurons.